(untitled) (Research, Society and Development, 2020)
Basil shows great importance due to the high content of bioactive substances present in the leaves, widely used in traditional medicine and the pharmaceutical industry. However, as in most plants, physiological and biochemical changes occur in drought-prone basil plants. Arbuscular mycorrhizal fungi (AMFs) have been used to minimize these changes. This study aimed to evaluate the growth and antioxidant response of basil plants under water deficit and inoculated with AMFs Clarideoglomus etunicatum. The study was carried out in a growth chamber on basil plants inoculated with AMFs and subjected to drought after 30 days after transplantation. Seedlings inoculated with AMF showed a colonization rate of 28.66 and 32.79%. Plants without AMFs inoculation and subjected to drought showed a significant reduction in stem diameter, shoot and root length, and shoot and root biomass accumulation. However, inoculation showed improved plant physiological response under water stress, increasing chlorophyll, and relative water content. Large amounts of proline have accumulated in the leaves of inoculated AMFs plants and under stress, which shows the beneficial role of these osmolites in basil subjected to drought. The antioxidant enzymes CAT and APX showed high activity in plants exposed to drought and inoculated with AMFs, which reduced the plasma membrane’s damage. AMFs in basil regulated the synthesis of osmolites and antioxidant metabolism positively, promoting drought tolerance.